2012
DOI: 10.1111/j.1442-9071.2012.02888.x
|View full text |Cite
|
Sign up to set email alerts
|

Topical ganciclovir treatment in patients with cytomegalovirus endotheliitis receiving penetrating keratoplasty

Abstract: Continuous topical 2% ganciclovir and a topical steroid adjusted by anterior inflammation are suggested after penetrating keratoplasty in all cases with cytomegalovirus endotheliitis to prevent cytomegalovirus recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 24 publications
0
24
0
Order By: Relevance
“…10 The treatment was applied every 2 to 3 hours daily as an induction therapy, and every 4 hours as a long-term maintenance therapy, as previously reported. 10 After the continual administration of topical ganciclovir for 3 months, all patients underwent another aqueous humor tap to perform a PCR test for detecting the presence of CMV. Topical ganciclovir was prescribed as a long-term antiviral therapy, without discontinuation.…”
Section: Topical Ganciclovir Treatment Of Patients With Cytomegalovirmentioning
confidence: 99%
See 3 more Smart Citations
“…10 The treatment was applied every 2 to 3 hours daily as an induction therapy, and every 4 hours as a long-term maintenance therapy, as previously reported. 10 After the continual administration of topical ganciclovir for 3 months, all patients underwent another aqueous humor tap to perform a PCR test for detecting the presence of CMV. Topical ganciclovir was prescribed as a long-term antiviral therapy, without discontinuation.…”
Section: Topical Ganciclovir Treatment Of Patients With Cytomegalovirmentioning
confidence: 99%
“…[1][2]17 In our daily practice, we use topical 2% ganciclovir as a long-term maintenance therapy without interruption for Posner-Schlossman syndrome patients with CMV-positive eyes. 10 Until now, no large-scale study of the long-term clinical outcomes in CMV-positive Posner-Schlossman syndrome patients has been reported. The In this report, we investigated the efficacy of a topical ganciclovir treatment on CMV-related Posner-Schlossman syndrome.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…It has previously been reported that GCV is effective in eliminating the CMV viral antigen, maintaining the control of IOP and preventing CEC loss in cases of CMV-positive PSS 16. It has also been reported that in patients with CMV endotheliitis who undergo corneal transplantation surgery, the postoperative recurrence of CMV is a serious complication that can lead to intractable graft failure 9. For patients suffering from corneal endothelial disease, DSAEK has now become the ‘treatment of choice’ to reduce graft rejection and long-term postoperative PKP-related complications.…”
Section: Discussionmentioning
confidence: 99%